Optimization Selection of Bit and Application Research on PDC + Motor Combination Drilling Technique in the Desert Oilfield. Issue 2 (August 2019) - Gang, Yu; Kun, Ning; Jinsong, Tong; Xiangji, Kong; feng, Qian; Junbiao, Liu; Huabei, Zhang
Abstract: The drilling speed has a lot to do with whether the selected bit type and formation type is matched. Choosing a reasonable drill bit type can achieve the goal of high speed and low cost drilling by improving drilling rate and reducing the occurrence of down hole trouble. On the basis of performance analysis of PDC bits, the linear relationship between rate of penetration and drilling footage is obtained. By means of the optimization of motor and parameters, the drilling parameters, such as weight on bit, torque, type of mud motor and operating temperature, are optimized by application in desert oilfield. It provides an effective reference for the rapid development of the same type of oilfield